The Impact of Peri-Urbanisation on Housing Development: Environmental Quality and Residents' Productivity in Ibeju-Lekki, Lagos - Adedire Funmilayo Mokunfayo; ADEGBILE MICHAEL BABATUNDE (Alanya Hamdullah Emin Paşa Üniversitesi, 2018)
This paper assesses the impact of peri-urbanisation on housing, environmental quality and residents’ socio-demography in Ibeju-Lekki peri-urban in Lagos, Nigeria. Primary data was collected through administration of 370 questionnaires to household heads in purposively selected sixteen settlements in the study area while secondary data was sourced from spatial images, land use maps and satellite images of the study area. Quantitative data were analysed using descriptive statistics while qualitative data was analysed using time series and satellite image analysis. The result shows a spatial expansion due mainly to increased housing development, a multi-dimensional environmental and socio-cultural challenges that impact negatively on the quality of living and a literate, high-income group dominance in the selected peri-urban settlements in Ibeju-Lekki. The study recommends the creation of a database to capture the pattern of housing development, residents’ socio-economic demography and infrastructure needs for intervention in policy design for sustainable development.